Alphabet Family Band - Jones, Sarah (Sarah Lucia) (Cincinnati, Ohio : Blue Manatee Press, 2017)
"ABCs, family, instruments! Three times the learning in one book! Explore all kinds of instruments, played by the whole family, in alphabetic rhyme"--Page [4] of cover.
Keywords: Musical instruments -- Juvenile fiction; Musical groups -- Juvenile fiction; Families -- Juvenile fiction; Alphabet -- Juvenile fiction; Musical instruments -- Fiction; Musical groups -- Fiction; Family life -- Fiction; Alphabet -- Fiction; Stories in rhyme